Novel host report for Catadiscus uruguayensis Freitas & Lent, 1939 (Trematoda, Diplodiscidae) infecting Austrolebias Costa, 1998 species from Uruguay - Vettorazzi, Renzo I. (2020)
The genus Catadiscus Cohn, 1904 has a total of 16 known species that infect the intestinal tract of reptiles, amphibians, and mollusks. However, Catadiscus has never been found in teleosts. The annual fish Austrolebias prognathus (Amato, 1986) and A. cheradophilus (Vaz-Ferreira, Sierra de Soriano & Scaglia de Paulete, 1965) were collected from temporary ponds in the southeast of Uruguay. The specimens found in the intestinal tract of these hosts were morphologically identified as Catadiscus uruguayensis Freitas & Lent, 1939, which until now were only known to infect amphibians. This work represents the first report of the genus Catadiscus infecting and developing in a fish host.